Current issues in libraries, information science and related fields - Woodsworth, Anne; Penniman, William David, 1937- (Advances in librarianship,, 2015)
This volume is unusual in that the theme is quite broad in scope yet focused on a specific topic; innovations and boundary-pushing studies in areas not usually found in library literature. It represents a look at the periphery of the field surveyed in previous volumes and presents chapters grouped into two categories: professional issues and transforming services. First section chapters include the challenges facing librarians in an age of litigiousness and threats to academic freedom, educating ethical leaders for the information society by adopting practices from business, valuing intellectual capital assets by looking at the role of librarians in a knowledge society, and emerging practices of open peer review as a means of achieving a "new science". In the second section chapters include the effects of terminology on health queries by analysing users health literacy and topic familiarity, an analysis of academic social networking via a case study of users information behaviour, a study on redefining services and spaces for graduate student success by creating a "scholars' commons", and a final chapter on serving adults and teens in social spaces within a "virtual branch".